Brachytherapy stents versus conventional plastic stents for the treatment of malignant ureteral obstruction: initial experience - Li, Yipu; Zhang, Chengzhi; Song, Mengyao; Sun, Zhanguo; Han, Xinwei; Zhou, Xueliang; Jiao, Dechao (Frontiers in Oncology, 2026)
ObjectiveTo evaluate the feasibility of a newly designed integrated plastic stent loaded with radioactive 125I seeds (brachytherapy stent) for the treatment of malignant ureteral obstruction (MUO).MethodsFrom May 2018 to May 2023, 30 patients with MUO underwent brachytherapy plastic stent placement (experimental group), while 41 patients underwent conventional plastic stent placement (control group). The primary endpoints were technical success, complications, the local disease response rate (DRR) and the gross haematuria control (GHC) rate; the secondary endpoints were the hydronephrosis Girignon score (HGC) and overall survival (OS).ResultsThe rates of technical success (100% vs. 100%), complications (26.7% vs. 14.6%) and HGC (1.5 ± 0.5) vs. (1.5 ± 0.5) in the experimental and control groups were not significantly different (p>0.05). The DRR (93.3% vs. 9.8%) and GHC rates (84.2% vs. 20.8%) of the experimental and control groups at 8 weeks were statistically significant (P<0.05). The OS [28.4 month (95% CI: 24.6–32.3) vs. 19.5 month (95% CI: 17.0–22.0)] of the experimental and control groups was significantly different (P<0.05).ConclusionThis novel brachytherapy stent is safe and effective for the treatment of MUO, but long term follow up is needed.